The Pathophysiology and Treatment of Pyoderma Gangrenosum—Current Options and New Perspectives - Łyko, Magdalena; Ryguła, Anna; Kowalski, Michał; Karska, Julia; Jankowska-Konsur, Alina (International journal of molecular sciences, 2024)
Pyoderma gangrenosum (PG) is an uncommon inflammatory dermatological disorder characterized by painful ulcers that quickly spread peripherally. The pathophysiology of PG is not fully understood; however, it is most commonly considered a disease in the spectrum of neutrophilic dermatoses. The treatment of PG remains challenging due to the lack of generally accepted therapeutic guidelines. Existing therapeutic methods focus on limiting inflammation through the use of immunosuppressive and immunomodulatory therapies. Recently, several reports have indicated the successful use of biologic drugs and small molecules administered for coexisting diseases, resulting in ulcer healing. In this review, we summarize the discoveries regarding the pathophysiology of PG and present treatment options to raise awareness and improve the management of this rare entity.